2015
DOI: 10.1002/jctb.4790
|View full text |Cite
|
Sign up to set email alerts
|

Two‐phase olive mill waste (alpeorujo) as carbon source for biosurfactant production

Abstract: BACKGROUND: The olive oil extraction process currently used in Spain and other Mediterranean countries generates large amounts of a semi-solid by-product known as 'alpeorujo' or 'two-phase olive mill waste' (TPOMW). Although TPOMW can be a source of valuable compounds, it is mostly dried and burnt to produce energy. This paper, and for the first time, reports the use of TPOMW as the main carbon source for the production of surfactin, a high added value biosurfactant, by Bacillus subtilis DSM 3256.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 45 publications
0
21
0
3
Order By: Relevance
“…However, the presence of residual oil and free sugars suggest that this waste could be used as carbon source for microbial growth. In two previous papers we have shown that OMW can be used as a carbon source for rhamnolipid and surfactin production, using strains of Pseudomonas aeruginosa and Bacillus subtilis respectively (Maass et al, 2015;Moya Ramírez et al, 2015). However, our results suggested that an optimisation of the production process is needed.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, the presence of residual oil and free sugars suggest that this waste could be used as carbon source for microbial growth. In two previous papers we have shown that OMW can be used as a carbon source for rhamnolipid and surfactin production, using strains of Pseudomonas aeruginosa and Bacillus subtilis respectively (Maass et al, 2015;Moya Ramírez et al, 2015). However, our results suggested that an optimisation of the production process is needed.…”
Section: Introductionmentioning
confidence: 68%
“…After that, surfactin concentration started to decrease in both cases. A maximum in surfactin concentration was also observed by Maass et al (2015).…”
Section: Kineticsmentioning
confidence: 77%
“…At the present time, alperujo is being re-used in composting, animal feed, or it is simply burned (Tortosa et al, 2012;Vitolo et al, 1999). However, since OMW contains residual oil not extracted in the primary processing, it is worth considering its use in the production of BS, an approach which has hardly been explored, with the exception of Mercadé et al (1993), who produced rhamnolipids using the liquid fraction of a three stage olive oil extraction as sole carbon source, and our first work (Maass et al, 2015), where we explored the possible production of surfactin from OMW. Therefore, the objective of our work is to explore the suitability of using OMW as a sole carbon source in the production of two biosurfactants: surfactin and rhamnolipid.…”
Section: Introductionmentioning
confidence: 99%
“…Biosurfactant production was carried out at 30 C in a culture medium adapted from Maass et al [15] , composed of 2% (v/v) of Trub, 0.1 of Ca , 0.1 of NaCl, 0.33 of 7 , 0.0017 of , 1.69 of , 0.50 of 7 , 0.90 of peptone and 7.0 of yeast extract. The pH of the medium was adjusted to 7.0 prior to sterilization at 121 C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The precipitated biosurfactant was centrifuged, washed twice with acidified water (pH 2.0) and resuspended in Milli-Q water (Millipore, USA). The pH of the solution was adjusted to 7.0, lyophilized, weighed and stored at 18 C [15] .…”
Section: Methodsmentioning
confidence: 99%